Stable transformation mediated by Agrobacterium tumefaciens in Jonquil is better than Agrobacterium rhizogenes - Yu, Wenjie; Tian, Haoran; Chen, Yifan; Lyu, Shanhua; Fan, Yinglun (Frontiers in Plant Science, 2025)
Agrobacterium tumefaciens-mediated genetic transformation has become an important method to study gene function and create new germplasm in plants. The classic genetic transformation process is time-consuming and laborious. In nature, some plants can propagate through detached leaves, which shows that the detached leaves can complete the dedifferentiation of leaf cell and bud differentiation through the intracellular hormone regulation of detached leaves without external hormones. Here, we report a simple leaf-cutting transformation (LCT) method without aseptic operation using Agrobacterium-mediated genetic transformation with detached leaves to complete the transgenic operation. Jonquil (Kalanchoe blossfeldiana), an ornamental plant with leaf propagation ability, was selected to transform via the LCT method using A. tumefaciens strain EHA105 and Agrobacterium rhizogenes K599. Without selection pressure, the visual reporter Ruby, a system for the biosynthesis of betalains, was used in the LCT method. New colorful germplasms of Jonquil accumulated with betalains were obtained. The transgenic Jonquils transformed by A. tumefaciens EHA105 grow normally, but these transgenic Jonquils transformed by A. rhizogenes K599 have abnormal growth, manifested as dwarf phenotype, and most Jonquils had protrusions like tentacles or polyps on their leaves. Stable transformation in Jonquil should be mediated by A. tumefaciens, not A. rhizogenes.